Toxic Masculinitites under the Microscope of Social Psychology Theory - Supratiwi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Reporting on sexual violence, domestic violence, and various other abusive behaviors has become one of the concrete outcomes caused by the existence of